An exploratory study of teachers' ICT competency at rural primary school in Sabah / Mohamad Asri Jumin - Jumin, Mohamad Asri (2015)
This study attempts to explore the teachers' level of ICT competency, the obstacles or challenges that hindering them to use of ICT in classroom and the factors that contribute to ICT competency by the in-service teachers in rural primary schools. Previous studies have found that the level of ICT competency of teachers in Malaysia was at the unsatisfactory level. This study employed the exploratory descriptive design which adopting quantitative as research approach. A survey questionnaire was conducted involving 114 in-service teachers at the eleven (11) rural primary schools in Ranau, Sabah. To support the finding in the survey, a simple observation also has been conducted. The finding of this study informed that these teachers' skills or competency in the usage of ICT was low but the teachers' perception on the obstacles that hinders them to use ICT in classroom was low. This means that they have a very high desire to integrate the ICT in classroom regardless the obstacles they are facing. This study also proved that to acquire or obtain skills in using ICT depending on collective factor such as support from the management, the teacher's desire or willingness to learn, the effective training and so on that related to the factor that contribute in build up the teachers competency in ICT.